Harnessing the potential of recycling architecture for sustainable development - Ma'rof, Aini Azeqa; Tan, Wei Xiang; Mohd Noor, Mohd Zairul (Human Resource Management Academic Research Society, 2024)
This article explores the transformative potential of recycling architecture in not just proposing recycle materials into building construction but also the integration of repurposing old buildings to address community needs within Malaysia's sustainable development framework. Amidst rapid urbanization and environmental concerns, recycling architecture offers a strategic avenue to alleviate resource scarcity and reduce environmental impact. Through an analysis of literature, case studies, and field observations, this study investigates the viability and benefits of repurposing old buildings to meet diverse community requirements. It examines how adaptive reuse, material recycling, and sustainable construction techniques can rejuvenate disused structures, serving as community hubs, educational facilities, or cultural spaces. Highlighting socio-economic and environmental advantages such as waste reduction, energy efficiency, and cultural preservation, repurposing old buildings fosters community revitalization and social cohesion. Despite regulatory and financial challenges, embracing recycling architecture presents opportunities for inclusive and sustainable community development. This research advocates for collaborative, culturally sensitive approaches in architectural design and urban planning to realize Malaysia's sustainable development goals. The article concludes with recommendations for policymakers, architects, developers, and communities to harness the potential of recycling architecture, emphasizing innovation and community engagement in repurposing old buildings for sustainable community development in Malaysia.